Baseball ballerina - Cristaldi, Kathryn; Carter, Abby (New York : Random House, 1992)
A baseball-loving girl worries that the ballet class her mother forces her to take will ruin her reputation with the other members of her baseball team.
"Grades 1-3"--Cover.
School Library Journal
Child Study Children's Book Committee
Booklist
1.9
K-3
Keywords: Ballet -- Fiction; Sex role -- Fiction; Baseball -- Fiction; Ballet -- Fiction; Sex role -- Fiction; Baseball -- Fiction